At the Origins of the Southern Question: Giacomo Tarascio’s Nazione e Mezzogiorno - Fresu, Gianni (International Gramsci Journal, 2023)
This is the abstract of a review in English by Gianni Fresu of the book by Giacomo Tarascio, Nazione e mezzogiorno. (Roma, Ediesse 2016).